Effectiveness of Acupuncture Used for the Management of Postpartum Depression: A Systematic Review and Meta-Analysis - Li, Wei (Biomed Res Int, 2019)
BACKGROUND: Previous studies have demonstrated that acupuncture was an effective alternative for treating major depressive disorders. However, the use of acupuncture for the treatment of postpartum depression remains controversial. This review summarizes the most significant studies in the area of acupuncture treatment for postpartum depression and provides a detailed overview of the efficacy of acupuncture for the treatment of postpartum depression. METHODS: We undertook a systematic review of publicly available electronic databases to identify studies that evaluated acupuncture for the treatment of postpartum depression. Our meta-analysis selected randomized controlled trials (RCTs) and quasi-RCTs that reported on the treatment effect of acupuncture on postpartum depression. RESULTS: Eight prospective trials reporting data on postpartum depression were included in our meta-analysis. The results demonstrated that acupuncture treatment could significantly reduce HAMD scores (SMD: -1.08; 95%CI: -2.11 to -0.05; P=0.040). However, with regard to EPDS, clinical response, and serum estradiol levels, pooled analysis suggested no beneficial effects of acupuncture for postpartum women in EPDS (RR: 1.23; 95%CI: 0.90 to 1.67; P=0.195); clinical response (RR: 1.00; 95%CI: 0.89 to 1.12; P=0.969); and the levels of serum estradiol (SMD: 1.96; 95%CI: -0.01 to 3.93; P=0.051). LIMITATIONS: First, there was relatively high heterogeneity among the studies, except for clinical response. In order to identify the sources of heterogeneity, we divided the studies into subgroups by way of controls. However, heterogeneity still existed, which suggested that it arose from participants rather than controls. Second, the sample size of the studies was small, causing the power of summary results to be low. This may result in over- or underestimating the interpretation of the results. Third, our analysis used pooled data, which restricted us from performing a more detailed analysis. CONCLUSIONS: Our meta-analysis suggested that acupuncture treatment may reduce HAMD scores, while no significant effects on EPDS, clinical response, and serum estradiol levels were observed.